2012
DOI: 10.3109/00016489.2012.727469
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular abnormality in patients with Meniere's disease and migrainous vertigo

Abstract: The abnormal rates in MD were significantly higher than those in MV. Of 45 MD patients, 21 (47%), 32 (71%), and 24 (53%) exhibited abnormal caloric, HSN, and VIN results, respectively. Fourteen (31%) MD patients had migraine associated with vertigo, but the association was not accompanied by high rates of abnormal results in the tests. Of 76 MV patients, 19 (25%), 38 (50%), and 24 (32%) exhibited abnormal caloric, HSN, and VIN results, respectively. Overall, 84% of patients with MD and 66% with MV exhibited ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 20 publications
4
46
2
2
Order By: Relevance
“…Our finding was the same. Moreover, the audiological, eye movement, and bithermal caloric test findings of the patients were similar to the literature [19,35,[37][38][39][45][46][47][48][49][50][51][52] . Head-shaking nystagmus has been reported as 60% previously, though the value was 20.4% in this study [38] .…”
Section: Discussionsupporting
confidence: 69%
“…Our finding was the same. Moreover, the audiological, eye movement, and bithermal caloric test findings of the patients were similar to the literature [19,35,[37][38][39][45][46][47][48][49][50][51][52] . Head-shaking nystagmus has been reported as 60% previously, though the value was 20.4% in this study [38] .…”
Section: Discussionsupporting
confidence: 69%
“…Despite the increasing number of studies related to VM, most of these reports have focused on the characteristics of the disease, including the results of neurotologic tests (3,10,17,18), and its treatment and prognosis related to the vestibular abnormalities have not yet been fully documented. It is important to understand the prognostic factors to predict the disease course with treatment and to properly counsel VM sufferers and conduct appropriate therapeutic planning.…”
Section: Objectivesmentioning
confidence: 97%
“…Vestibular abnormality resulting in episodic vertigo can also trigger migraine headaches, indicating that vertigo itself may act as a migraine trigger (8,9). In this regard, vestibular abnormality is frequent in VM patients, suggesting a significant role of vestibular abnormalities in this condition (10).…”
Section: Objectivesmentioning
confidence: 98%
“…Studies have reported abnormal SVV findings in the Ménière's disease, vestibular neuritis, gentamycin toxicity, and after stapedectomy [23][24][25][26] . VM is the second most common cause of dizziness [27] .…”
Section: Discussionmentioning
confidence: 99%